2018
DOI: 10.2147/ccid.s158129
|View full text |Cite
|
Sign up to set email alerts
|

The impact of acne and facial post-inflammatory hyperpigmentation on quality of life and self-esteem of newly admitted Nigerian undergraduates

Abstract: BackgroundAcne and facial post-inflammatory hyperpigmentation are relatively common clinical conditions among adolescents and young adults, and inflict psychosocial injuries on sufferers.ObjectiveTo document the psychosocial and self-esteem implications of acne and facial hyperpigmentation on newly admitted undergraduates.Materials and methodsA cross-sectional survey was conducted among 200 undergraduates. Demographics and clinical characteristics were obtained and acne was graded using the US Food and Drug Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 22 publications
4
45
1
1
Order By: Relevance
“…The findings of high prevalence of mild to moderate acne vulgaris were consistent with many studies. A similar pattern was obtained in comparative studies done in Queens Medical Centre, Nottingham in UK where (50%) were rated by the researcher as having no acne, (22%) as having very mild acne, (17%) as having mild acne and 34 (11%) as having moderate to severe acne [7], another study conducted in Nigeria showed only one student had severe acne vulgaris (GAGS, 31-38), 10% moderate (GAGS, 19-30), and 89.4% mild (GAGS, 1-18) [8]. The mean age of acne vulgaris among participants was 16 year old which is similar to findings documented in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of high prevalence of mild to moderate acne vulgaris were consistent with many studies. A similar pattern was obtained in comparative studies done in Queens Medical Centre, Nottingham in UK where (50%) were rated by the researcher as having no acne, (22%) as having very mild acne, (17%) as having mild acne and 34 (11%) as having moderate to severe acne [7], another study conducted in Nigeria showed only one student had severe acne vulgaris (GAGS, 31-38), 10% moderate (GAGS, 19-30), and 89.4% mild (GAGS, 1-18) [8]. The mean age of acne vulgaris among participants was 16 year old which is similar to findings documented in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Two hundred Nigerian young students completed CADI and RSES questionnaires in 2018 in a survey conducted by Akinboro et al . The level of anxiety and emotional distress is significantly different between the groups with acne with facial hyperpigmentation and in those with acne but without hyperpigmentation.…”
Section: Resultsmentioning
confidence: 99%
“…This is comparable to other studies that have shown that the presence of skin conditions affects the quality-of-life of an individual significantly. [26,27] Skin disorders have been shown to lead to low self-esteem, feelings of shame, guilt, and at times, social isolation. [26,27] Dermatological lesions are often not hidden in many instances, and the affected individuals usually have to realistically live with the constant reality that they have a problem or challenge which others readily know and/or talk about.…”
Section: Annals Of Health Research Volume 7 Issue No 1 2021_______mentioning
confidence: 99%